Associations Between Bone Mineral Density, Grip Strength, and Lead Body Burden in Older Men. Issue 1 (2nd January 2014) - Khalil, Naila; Faulkner, Kimberly A.; Greenspan, Susan L.; Cauley, Jane A.
<x xml:space="preserve">Abstract</x> Objectives To study the association between blood lead concentration (BPb) and bone mineral density (BMD), physical function, and cognitive function in noninstitutionalized community‐dwelling older men. Design Cross‐sectional study. Setting University of Pittsburgh clinic, Pittsburgh, Pennsylvania. Participants Non‐Hispanic Caucasian men aged 65 and older (N = 445) recruited as a subset of a prospective cohort for the Osteoporotic Fractures in Men Study. Measurements BPb was measured in 2007/08. From 2007 to 2009, BMD (g/cm2) was measured using dual‐energy X‐ray absorptiometry. At the same time, physical performance was measured using five tests: grip strength, leg extension power, walking speed, narrow‐walk pace, and chair stands. Cognitive performance was assessed using the modified Mini‐Mental State Examination and the Trail‐Making Test Part B. Participants were categorized into quartiles of BPb. Multivariate regression analysis was used to evaluate the independent relationship between BPb, BMD, and cognitive and physical function. Results Mean BPb ± standard deviation was 2.25 ± 1.20 μg/dL (median 2 μg/dL, range 1–10 μg/dL). In multivariate‐adjusted models, men in higher BPb quartiles had lower BMD at femoral neck and total hip (P‐trend < .001 for both). Men with higher BPb had lower age‐adjusted score for grip strength (P‐trend < .001), although this association was not significant in multivariate‐adjusted models (P‐trend < .15). BPb was not associated with lumbar spine BMD, cognition, leg extension power, walking speed, narrow‐walk pace, or chair stands. Conclusion Environmental lead exposure may adversely affect bone health in older men. These findings support consideration of environmental exposure in age‐associated bone fragility.